Integrated Disease Management of Tomato Late Blight (Nepal Agriculture Research Journal, 2014)
Tomato late blight caused by Phytophthora infestans (Mont.) de Bary is a  serious disease of tomato and potato worldwide. The disease causes severe  crop losses in the tomato growing regions of the world. Most of the cultivars  grown in the world are reported to be susceptible to late blight. Systemic  fungicides have been used widely in the past, but the disease has developed  resistance over time. The present study was carried out to minimize  fungicide use through integrated pest management. The bio-pesticides  Azadirachta indica (Neem), Artemisia vulgaris (Mugwort) and Trichoderma  viride were tested along with the fungicides Krilaxyl (metalaxyl 8% and  mancozeb 64%) and Dithane M-45 (mancozeb 80%) in Nepal during 2000  and 2001. All three bio-pesticides were found more effective than the control  in reducing development of the disease and they increased yield over the  control by 17 to 41%. However, the fungicides, Krilaxyl and Dithane M-45  were observed even more effective. Two transplanting dates ie first and third  week of July were tested against late blight in rainy season during 2000and  2001 and observed its effect on yields. Lower disease incidence and better  yield were found in the second planting.  Nepal Agric. Res. J. Vol. 8, 2007, pp. 67-76DOI: http://dx.doi.org/10.3126/narj.v8i0.11583